Ayurvedic insights into the early pathogenesis and management of ankylosing spondylitis: a case report - M. R., Silpa; Krishnan N., Navaneeth; T. C., Marikutty (International Journal of Research in Medical Sciences, 2025)
Ankylosing spondylitis is a chronic seronegative inflammatory arthritis that mainly affects the sacroiliac joints and spine, potentially leading to spinal fusion. Conventional treatments like NSAIDs, DMARDs, and TNF-α inhibitors help manage pain and inflammation but do not provide a cureIn this case 37year old male patient admitted in kayachikitsa inpatient department of vaidyaratnam ayurveda college, ollur on 02/01/24 with pain and restricted movements of neck, swelling with pain on right knee joint and low back ache. He was diagnosed as ankylosing spondylitis (Sandhigata vata) as per Modified New York Criteria for Ankylosing spondylitis (AS) and including the clinical presentation, physical examination, laboratory tests. He underwent treatment protocol of vatavyadhi chikitsa. Ayurvedic preparations like chitrakadi kashayam, maharasnadi kashayam, chandrapraba gulika, vettumaran gulika, shaddharanam choornam were given internally. Dhanyakizhi, lepanam, dhanyamla dhara, abhyangam were given as external therapy. Visual analogue scales for pain, range of movements, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Ankylosing Spondylitis Disease Activity Score using ESR (ASDAS-ESR), AMA assessment tool were used to evaluate the effectiveness of the treatment. After the treatment patient got relief of pain, considerable improvement in range of motion of cervical spine, swelling and pain on right knee joint reduced. This case study highlighted that within 2 weeks restricted movements of neck got considerable improvement and ankylosing spondylitis disease activity score using ESR (ASDAS-ESR) decreased significantly by conservative ayurvedic management only.